ESSENTIAL OIL COMPOSITION AND ANTIOXIDANT, ANTICANCER ACTIVITIES OF ARTEMISIA SANTOLINIFOLIA (Pamp) GROWN IN MONGOLIA - Altangerel, Bayanmunkh; Jambal, Irekhbayar; Sarangerel Oidovsambuu; Altantsetseg Shatar (IJRDO-Journal of Applied Science, 2025)
Medicinal plants have always been considered a healthy source of life for all people. In Mongolia, the use of various medicinal and food plants has a long history. In recent years, interest in plant-derived food additives has grown. This study was designed to determine essential oil chemical composition and evaluate antioxidant, cytotoxic activities of aerial parts serial fractions from Artemisia santolinifolia grown in Mongolia. The chemical composition of essential oil from A. santolinifolia was determined by GC-MS analysis. Among them 49 components b-thujene (47.89%), sabinene ketone (11.78%), a-thujene (3.98%), terpinen-4-оl (2.34%) were found to be the major ones. The ethanol crude extract of A.santolinifolia was suspended in water and consequently fractionated with n-hexane, chloroform, ethyl acetate and butyl alcohol. All the fractions were examined for their antioxidant and protective effect against tert-butylhydroperoxide-induced cell death by using DPPH and MTT assays, respectively. Ethyl acetate fraction showed the highest DPPH radical scavenging activity at a concentration of 50 µg/ml by 91.67% with the IC50 value of 12.03 µg/ml. MTT results showed that ethyl acetate, butanol and water fractions demonstrated significant protective effect against the oxidative stress in HepG2 cell line. These suggest that the fractions of A. santolinifolia could hold a good potential for use in the pharmaceutical industry.